Case report: A clinical report of photodynamic neoadjuvant combined with fluorescent laparoscopic localization robotic surgery for the treatment of patients with advanced colorectal cancer combined with obstruction - Huang, Xiaodong; Han, Xiaowen; Li, Weidong; Zhang, Jiayi; Ma, Bin; Wang, Yuhan; Yin, Zhenyu; Gao, Lei; Shi, Jianming; Maswikiti, Ewetse Paul; Chen, Hao (Frontiers in Immunology, 2024)
The incidence of colorectal cancer is relatively high in our country, with the majority of patients being diagnosed at an advanced stage. For individuals with advanced-stage colorectal cancer, conversion or neoadjuvant therapy is frequently necessitated to facilitate surgical intervention and achieve a curative effect. And about 10% to 30% of colon cancer patients are complicated with intestinal obstruction. Surgical intervention remains the primary treatment for managing intestinal obstructions, albeit with a considerable risk of perioperative mortality and an increased likelihood of postoperative complications. PDT, as a neoadjuvant treatment for colon cancer, can shrink the local tumor and relieve obstruction, and is effective in colon cancer combined with obstruction. Robotic surgery has the advantages of high stability and low trauma, and compared with laparoscopic colon cancer surgery, robotic surgery can achieve better results. Fluorescent laparoscopic clarifies the location and size of the tumor lesion, allowing for greater precision when removing colon cancer lesions in robotic surgery. Therefore, in the treatment of colon cancer, PDT can offer an opportunity for surgery after relieving obstruction in patients with obstructive colon cancer. Additionally, when combined with fluorescent laparoscopic robotic colon cancer surgery, it provides a novel treatment approach for patients with obstructive colon cancer. Preoperative photodynamic neoadjuvant therapy combined with robotic colon cancer surgery has not yet been reported. Here, we report a case of colon cancer with obstruction，preoperative TNM stage was T4N1, and the lesion had caused intestinal stenosis. After four sessions of PDT, the patient's intestinal lumen was unobstructed and the lesion had regressed. After evaluation, fluorescent laparoscopic localization and visualization of lymph nodes combined with robotic colon cancer resection were performed. Postoperative pathology showed that the patient's tumor regression grade was grade 1. The patient's tumor was completely resected with good resection effect. No tumor invasion was found on both sides of the resection margin, and the patient did not relapse after surgery.